2013
DOI: 10.3389/fpsyg.2013.00108
|View full text |Cite
|
Sign up to set email alerts
|

Category Processing and the human likeness dimension of the Uncanny Valley Hypothesis: Eye-Tracking Data

Abstract: The Uncanny Valley Hypothesis (Mori, 1970) predicts that perceptual difficulty distinguishing between a humanlike object (e.g., lifelike prosthetic hand, mannequin) and its human counterpart evokes negative affect. Research has focused on affect, with inconsistent results, but little is known about how objects along the hypothesis’ dimension of human likeness (DHL) are actually perceived. This study used morph continua based on human and highly realistic computer-generated (avatar) faces to represent the DHL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 107 publications
7
61
2
Order By: Relevance
“…Consistently, one image morphing study has demonstrated that human-likeness manipulations of eyes explain most (albeit not all) of the perceived animacy of faces (Looser and Wheatley, 2010). Similarly, one eye tracking study has demonstrated that eyes receive longer gaze dwell time on categorically ambiguous than on categorically unambiguous artificial faces (Cheetham et al, 2013). To our knowledge, the previous suggestion that negative affinity would be caused by inconsistent static and dynamic information (Brenton et al, 2005; Pollick, 2010) also remains unexplored.…”
Section: Discussionmentioning
confidence: 95%
“…Consistently, one image morphing study has demonstrated that human-likeness manipulations of eyes explain most (albeit not all) of the perceived animacy of faces (Looser and Wheatley, 2010). Similarly, one eye tracking study has demonstrated that eyes receive longer gaze dwell time on categorically ambiguous than on categorically unambiguous artificial faces (Cheetham et al, 2013). To our knowledge, the previous suggestion that negative affinity would be caused by inconsistent static and dynamic information (Brenton et al, 2005; Pollick, 2010) also remains unexplored.…”
Section: Discussionmentioning
confidence: 95%
“…It predicts that the "difficulty distinguishing between a humanlike object and its natural human counterpart will evoke negatively valenced feelings and cognitions" [8, p. 1], known as the "uncanny valley". We define human likeness as the extent to which robots more closely resemble people that also includes the physical humanlike similarity to robots [29,8]. Figure 3 depicts the human perception of different entities in dependence to the degree of human likeness.…”
Section: Uncanny Valley Paradigm the Uncanny Valley Paradigm Was Firmentioning
confidence: 99%
“…The categorical perception hypothesis is in line with insights from evolutionary biology linking categorization to survival and the failure to categorize stimuli to negative emotional responses (Burleigh & Schoenherr, 2015). Psychological research has further demonstrated that category boundaries exist for identification of facial images along morphed spectra (Cheetham, Pavlovic, Jordan, Suter, & Jancke, 2013;Cheetham et al, 2011;Cheetham, Suter, & Jancke, 2014;Looser & Wheatley, 2010;Yamada, Kawabe, & Ihaya, 2013; see Figure 1 for an illustration of the category boundary concept), and that discrimination performance reaches its peak when agent images straddle the category boundary, indicating categorical ambiguity (Cheetham et al, 2011(Cheetham et al, , 2014Looser & Wheatley, 2010). Increased categorical ambiguity has been reported to coincide with negative stimulus evaluations in some studies (Burleigh, Schoenherr, & Lacroix, 2013;Ferrey, Burleigh, & Fenske, 2015;Yamada et al, 2013) but not in others (Cheetham et al, 2014;Looser & Wheatley, 2010;.…”
Section: Introductionmentioning
confidence: 57%